An Analysis of the Sustainability Performance of Indonesian Banks and Islamic Financial Institutions Using a Triple Bottom Line Model - Yusmaniarti Yusmaniarti; Fitri Santi; Nurna Aziza; Husaini Husaini; Ridwan Nurazi; Fadli Fadli (East Asian Journal of Multidisciplinary Research, 2023)
The Triple Bottom Line-based Sustainability Performance model in Indonesian Islamic banks and financial institutions is the subject of this dissertation research. Using theoretical vantage points from resource dependency theory, interest theory, agency theory, institutional theory, and legitimacy theory, this study investigates the impact of Islamic Corporate Governance (ICG) on Corporate Sustainability Performance (SP), which employs Islamic corporate governance mechanisms. It primarily focuses on sharia board attributes and ownership structure. Regression analysis is done in this study using Eviews 10, and thirteen recommendations are made to enhance sustainability performance. By visiting each company's official website and the website www.idx.co.id, secondary data was gathered. 49 Islamic financial institutions that were registered with the OJK between 2016 and 2021 comprised the research sample of Indonesian Islamic banks and financial institutions. Data from financial reports were used for six years, making 294 total samples of data from the panel. This study will look at the characteristics of the Sharia Board (DS), which will be used as independent variables. The Corporate Sustainability variable will be used as a dependent variable, and the variables Independent Sharia Board, size of the Sharia Board, Sharia Board Meetings, Gender Diversity, and the existence of a sustainability committee and the application of AAOIFI standards will be used as proxies. The research results show that Indonesian Islamic corporate governance has a significant effect on sustainability performance, with Independent sharia boards, Gender diversity, and AAOIFI implementation being able to influence sustainability performance while size, board meetings, and sustainability committees do not influence the sustainability performance of Islamic banks and financial institutions in Indonesia. Institutional ownership is partially able to moderate the relationship between independent sharia boards, gender diversity and implementation with sustainability performance. Institutional ownership is unable to moderate the size of the sharia board, sharia board meetings and sustainability committee on sustainability performance. This research provides policy insights for policymakers, practitioners, and corporate boards to promote sustainable operations through Islamic corporate governance, adding to existing development plans to address sustainability-related issues. This research contributes to the literature by establishing a relationship between Islamic corporate governance and triple-bottom-line performance in Indonesian Islamic banks and financial institutions